Social and endocrine correlates of immune function in meerkats: implications for the immunocompetence handicap hypothesis. Issue 8 (1st August 2018) - Smyth, Kendra N.; Caruso, Nicholas M.; Davies, Charli S.; Clutton-Brock, Tim H.; Drea, Christine M.
Abstract : Social status can mediate effects on the immune system, with profound consequences for individual health; nevertheless, most investigators of status-related disparities in free-ranging animals have used faecal parasite burdens to proxy immune function in the males of male-dominant species. We instead use direct measures of innate immune function (complement and natural antibodies) to examine status-related immunocompetence in both sexes of a female-dominant species. The meerkat is a unique model for such a study because it is a cooperatively breeding species in which status-related differences are extreme, evident in reproductive skew, morphology, behaviour, communication and physiology, including that dominant females naturally express the greatest total androgen (androstenedione plus testosterone) concentrations. We found that, relative to subordinates, dominant animals had reduced serum bacteria-killing abilities; also, relative to subordinate females, dominant females had reduced haemolytic complement activities. Irrespective of an individual's sex or social status, androstenedione concentrations (but not body condition, age or reproductive activity) negatively predicted concurrent immunocompetence. Thus, dominant meerkats of both sexes are immunocompromised. Moreover, in female meerkats, androstenedione perhaps acting directly or via local conversion, may exert a double-edged effect of promoting dominance and reproductive success at the cost of increased parasitism and reduced immune function. Given the prominent signalling of dominance in female meerkats, these findings may relate to the immunocompetence handicap hypothesis (ICHH); however, our data would suggest that the endocrine mechanism underlying the ICHH need not be mediated solely by testosterone and might explain trade-offs in females, as well as in males.